Spatial Analysis of Renewable Energy Sources - Kacare Marika (Sciendo, 2021)
Renewable energy sources are expanding opportunities for industrial development and can boost economic growth and create new jobs. In all European Union (EU) countries, including Latvia, it is possible to use renewable energy resources cost-effectively. The world is now at the beginning of the global energy transformation. Cost-effective renewable energy technologies provided an opportunity for sufficient development to reach ambitious climate targets of the EU Directive 2009/28/EC. Some systems are not only dependent on the interaction of many elements and dynamics over time, but they are also variable in space. In this context, energy production from local and renewable resources is one of the most relevant examples. It is characterized by many spatially variable elements, such as biomass availability, wind speed, solar radiation, location of power plants, transmission network infrastructure, energy demand, etc. It is crucial to explore the spatial distribution of resources to plan territorially-unified development of renewable energy and, consequently, promote efficient use of resources. This paper describes the data acquisition process of the spatial distribution of renewable energy sources. ArcGIS PRO and data collected from the various databases were used to describe the energy sectors according to resources, spheres of consumption and regions.